Competitiveness of African agricultural exports - Odjo, Sunday P.; Badiane, Ousmane (International Food Policy Research Institute, 2018)
Chapter 4, by Sunday Pierre Odjo and Ousmane Badiane, presents a detailed analysis of the competitiveness of African agricultural exports in global and regional markets. The chapter aims to shed light on the factors behind recent improvements in trade performance in order to further accelerate gains and reduce trade deficits. The study ranks countries and commodities according to their competitiveness in export markets at the global, continental, and REC levels. The chapter then summarizes an econometric analysis of the drivers of changes in competitiveness at different levels, and presents recommendations for further improving competitiveness.